Electrochemical detection of mercury using biosynthesized hydroxyapatite nanoparticles modified glassy carbon electrodes without preconcentration1. Issue 84 (16th September 2015) - Kanchana, P.; Sudhan, N.; Anandhakumar, S.; Mathiyarasu, J.; Manisankar, P.; Sekar, C.
<x xml:space="preserve">Abstract</x> An electrochemical method for the determination of trace levels of mercury(ii) ions using Aloe vera (Av) assisted hydroxyapatite (HA) nanoparticles modified glassy carbon electrode (GCE) by square wave voltammetry is described for the first time.